Laparoscopic splenectomy experience in the University Hospital ‘‘Dr. José Eleuterio González’’ - Cueto Ramos, Rubén Gerardo; Muñoz Maldonado, Gerardo Enrique; Hernández Guedea, Marco Antonio; Fernández Treviño, J. R.; Limas Rodríguez, Q. G. (UANL. Facultad de Medicina, 2015)
To present the laparoscopic splenectomy (LS) experience at the ‘‘Dr. José E. González’’ University Hospital from January 2008 to October 2014. Methods: Retrospective and descriptive analysis of clinical and surgical aspects of all patients who underwent laparoscopic splenectomy from January 1st 2008 to October 31st 2014 at the ‘‘Dr. José Eleuterio González’’ University Hospital. Results: Laparoscopic splenectomies were performed on 14 patients, with a mean age of 20.6 years. Indications for splenectomy included the following diagnosis: idiopathic thrombocytopenic purpura (ITP), 71%; hereditary spherocytosis, 14%; sickle cell anemia and thalassemia, 7%; pyruvate kinase deficient hemolytic anemia, 7%. Mean operative time was 177.5 min. Mean intraoperative hemorrhage was 223.5 ml. Conversion to laparotomy occurred in one patient (7%) associated with uncontrollable bleeding with splenomegaly. Accessory spleens were identified in 3 patients (21%). Mean spleen weight was 187.5 g. Mean postoperative hospital stay was 3.35 days. There was no surgical re-intervention. The 4 trocar right lateral decubitus approach was the preferred method for all patients. Conclusions: LS can be performed as a safe and effective procedure in benign hematological diseases in our everyday environment.